Management Issues of HIV Infection in Poor Resource Setting Due to Unavailability of Drug Sensitivity Testing - Ahmadu, Baba Usman (Journal of Nepal Paediatric Society, 2013)
Despite the obvious benefits that rapid scale-up of antiretroviral therapy (ART) has had on cases of human immunodeficiency virus (HIV), treatment failure that is mostly associated with the emergence of HIV drug resistance still remains a major challenge. Index case is a stage 4 HIV patient who failed multiple ART, including nucleoside and nonnucleoside reverse transcriptase inhibitors (NRTIs and NNRTIs) and protease inhibitors (PIs). His clinical and immunological markers continued to fail despite completion of anti tuberculosis drugs, adequate nutrition, and treatment for opportunistic infections. This case indicates an emerging need to consider providing facility for HIV drug sensitivity testing at various sites in order to select appropriate second line antiretrovirals that would be of benefit to a patient. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7699 J Nepal Paediatr Soc. 2013; 33(2):141-143